Brick tea consumption and its relationship with fluorosis in Tibetan areas - Wen, Cai; Zhang, Qing; Xie, Fei; Jiang, Jixin (Frontiers in Nutrition, 2022)
Brick tea-type fluorosis (BTF) due to a high intake of brick tea is possible in Tibetan populations, and dental fluorosis (DF) and skeletal fluorosis (SF) are its primary manifestations. To determine the prevalence of DF and SF and their relationships with brick tea intake in Tibetan populations, a literature review was conducted for studies published between 1994 and 2021. The available evidence revealed that brick tea may be produced from older stems and leaves of the tea plant and that the fluoride content of brick tea exceeds the national standard. The harsh environment of the plateau has led to limited food sources for the local Tibetan people who form the habit of drinking tea leaves as a satiation solution to digest greasy food and replenish vitamins, and regular consumption of brick tea leads to excessive exposure of Tibetan residents to fluoride. Studies in Tibet showed that the prevalence of DF in children was 14.06–75.93% in different districts, and the overall pooled prevalence of DF was 26.08%. The prevalence of SF in adults was 19.90–74.77% in different Tibetan districts, and the overall pooled prevalence of SF was 33.84%. The analysis of risk factors showed that the prevalence of BTF may be related to high altitude and different working and living conditions, and BTF in children may be associated with fluoride intake during mothers’ pregnancy and lactation. With the development of bioinformatics research, gene polymorphisms were suspected to be related to susceptibility to fluorosis in Tibetan populations. The study of BTF in Tibetan people needs to be further investigated and standardized, and additional studies evaluating the pathogenesis and preventive measures of BTF are warranted.